Baby Shaming as a Cyberbullying Phenomenon Against Babies Through Social Media - Mariatul Qibtiyah; Alva Beriansyah; Irmawati Sagala (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The phenomenon of baby shaming is common in our society. Baby Shaming is a form of bullying aimed at babies and toddlers. Although the impression of baby shaming only means joking and small talk, in fact baby shaming is a form of verbal violence that comes from words and comments on social media and is included as cyberbullying because it can offend and even hurt the parents of the baby or toddler who is the victim of baby shaming. Using the netnography research method in an online qualitative approach, this article looks at the phenomenon of baby shaming that occurs on the Instagram accounts of Indonesian artists, namely Tasya Kamila and Shandy Aulia. These two artists who have babies/toddlers experience cyberbullying in the form of baby shaming by netizens. Cyberbullying in the form of baby shaming occurs because society has ideal standards that are seen from body parts such as body size (too thin, fat, short, tall), limb shape (stomach, chest, teeth), skin color (black, white), to hair (thin, curly, bald, infertile). Baby shaming in the form of cyberbullying that occurs through social media can be categorized as a criminal offense that has been regulated in Law Number 19 of 2016 concerning Electronic Information and Transactions (ITE Law). This baby shaming will have an impact, especially for the baby's mother both psychologically and socially. There are several things that can be done if you experience this baby shaming, namely not blaming yourself, focusing on child development, and also closing social media accounts and also being ignorant. Whether the comments are in person or through the media, baby shaming can still be categorized as bullying so the culture of small talk that leads to baby shaming must be stopped. Keywords: Baby Shaming; Cyberbullying; Social Media